(1113) A Programming Approach the Problem of Supply Response اسلوب البرمجة لمشكلة الاستجابة للعرض - Mohaya A. Zaytoun. (INP., 2018)
This study reviews the primary methodologies used in the analysis of agricultural supply response. Empirical research in this field generally falls into two main categories: econometric analysis and mathematical programming. Econometric approaches, often termed historical or positive analyses, rely on statistical models to identify relationships between past and future producer behavior, enabling the prediction of future supply patterns. In contrast, mathematical programming methods, associated with normative analysis, are based on the principle of profit maximization and emphasize the technical and structural aspects of production rather than historical trends. By examining both approaches, this study highlights the different perspectives they offer on the dynamics of agricultural supply adjustment.